PENGENALAN PROFESI AKUNTAN UNTUK MENINGKATKAN MINAT BELAJAR SANTRI PADA PONDOK PESANTREN AS-SAIDIYAH NW DESA TEMPOS - Pratiwi, Widya; Syukri, Muhammad; Pahmi, Saepul; Prabowo, M. Bogie Rizki; Susilawati, Susilawati; Banuaji, Datu Azura (LPPM Institut Pendidikan Nusantara Global, 2023)
Students with high motivation to study have a tendency to study harder. This PKM aims to foster the motivation to learn students (santri) at the As-saidiyah NW Tempos Islamic boarding school through the introduction of various accountant professions. Pesantren is a comprehensive institution in terms of both curriculum and learning process. Along with the times, pesantren must also be able to follow the development of technology and information. Similarly, in the field of accounting knowledge, this field is also required to be able to adapt to the development of information technology that occurs. In the accounting profession, which is a problem not only because of technological developments but also because of the lack of socialization and promotion related to the output of the accounting department, so that students experience confusion in determining their interests and expected professions. Therefore, more intense socialization related to the accountant profession is needed. This service is carried out by visiting the As-saidiyah Islamic boarding school directly to provide socialization to students related to the accountant profession. This socialization is aimed at convincing them that accountants are a profession with many opportunities. After the presentation of the material, a discussion and question and answer session was opened, from the results of the discussion showed that by knowing various kinds of accountant professions, their enthusiasm for learning increased, because many students from the As-saidiyah Islamic boarding school were interested in becoming accountants.